2020
DOI: 10.1016/j.ijpddr.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A new paraprobiotic-based treatment for control of Haemonchus contortus in sheep

Abstract: Haemonchus contortus is a critical parasite of goats and sheep. Infection by this blood-feeding gastrointestinal nematode (GIN) parasite has significant health consequences, especially in lambs and kids. The parasite has developed resistance to virtually all known classes of small molecule anthelmintics used to treat it, giving rise in some areas to multidrug resistant parasites that are very difficult to control. Thus, new anthelmintics are urgently needed. Bacillus thuringiensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…1 B). As has been shown with all other parasitic nematodes tested [ 31 , 47 ], intoxication of A. suum by Cry5B IBaCC was dependent upon Cry5B protein since incubation of parasites in the presence of IBa control lacking Cry5B but otherwise identical to IBaCC resulted in no intoxication (detailed in Materials and Methods). These in vitro data indicated that Cry5B IBaCC, but not the inactivated bacterium B. thuringiensis with empty vector (IBa), has potential to impact A. suum infections in vivo .…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…1 B). As has been shown with all other parasitic nematodes tested [ 31 , 47 ], intoxication of A. suum by Cry5B IBaCC was dependent upon Cry5B protein since incubation of parasites in the presence of IBa control lacking Cry5B but otherwise identical to IBaCC resulted in no intoxication (detailed in Materials and Methods). These in vitro data indicated that Cry5B IBaCC, but not the inactivated bacterium B. thuringiensis with empty vector (IBa), has potential to impact A. suum infections in vivo .…”
Section: Resultssupporting
confidence: 59%
“…Continuing human MDA campaigns and veterinary parasite control strategies would therefore benefit substantially with the addition of new anthelmintics against ascarid parasites with the following requirements: highly and broadly potent against this family of helminths, and safe, inexpensive, and massively scalable for MDA. We have recently described an active pharmaceutical ingredient (API) called IBaCC (see below) containing the Bacillus thuringiensis (Bt) Crystal (Cry) protein Cry5B that is effective against human hookworm infections in rodents and against Haemonchus contortus infections in sheep and that meets all the requirements for MDA [ 31 , 32 ]. Cry5B itself was shown to be active against A. suum in pigs when delivered as a live spore-crystal lysate (SCL) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…On a molar concentration scale, Cry5B IBaCC is 175× more effective at clearing hookworms than albendazole ( 66 ). High efficacy of Cry5B IBaCC against Haemonchus contortus infections in small ruminants (sheep) has also just been reported ( 67 ).…”
Section: Discussionmentioning
confidence: 94%
“…Haemonchus contortus is a nematode parasite that feeds on the blood of ruminants as a source of nutrition, causing serious effects and even death to grazing ruminants worldwide, especially to small ruminants [ 47 , 48 ]. In this study, we cloned and expressed the gene encoding HcGOB, a key enzyme of the trehalose synthesis pathway of H. contortus and found that the rHcGOB protein was recognized by the sera from a goat infected with H. contortus .…”
Section: Discussionmentioning
confidence: 99%